The Excavations of the University of Milan at the Bronze Age Site of Lavagnone (Desenzano del Garda, BS) (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2014)
This paper briefly presents the archaeological research of the University of Milan in the Bronze Age pile-dwelling site of Lavagnone. The excavation camps are directed by the Prehistoric and Proto-historic professorship and are opened to all students of Cultural Heritage and Archaeology, offering an important and formative experience in the field of stratigraphic excavation.
Keywords: Prehistory; Proto-history; Bronze Age; dwelling sites; Terramare; Lavagnone